Combined local and systemic bleomycin administration in electrochemotherapy to reduce the number of treatment sessions - Maglietti, Felipe Horacio (2016)
Background. Electrochemotherapy (ECT), a medical treatment widely used in human patients for tumor treatment, increases bleomycin toxicity by 1000 fold in the treated area with an objective response rate of around 80%. Despite its high response rate, there are still 20% of cases in which the patients are not responding. This could be ascribed to the fact that bleomycin, when administered systemically, is not reaching the whole tumor mass properly because of the characteristics of tumor vascularization, in which case local administration could cover areas that are unreachable by systemic administration. Patients and methods. We propose combined bleomycin administration, both systemic and local, using companion animals as models. We selected 22 canine patients which failed to achieve a complete response after an ECT treatment session. Eleven underwent another standard ECT session (control group), while 11 received a combined local and systemic administration of bleomycin in the second treatment session. Results. According to the WHO criteria, the response rates in the combined administration group were: complete response (CR) 54% (6), partial response (PR) 36% (4), stable disease (SD) 10% (1). In the control group, these were: CR 0% (0), PR 19% (2), SD 63% (7), progressive disease (PD) 18% (2). In the combined group 91% objective responses (CR+PR) were obtained. In the control group 19% objective responses were obtained. The difference in the response rate between the treatment groups was significant (p < 0.01). Conclusions. Combined local and systemic bleomycin administration was effective in previously to ECT non responding canine patients. The results indicate that this approach could be useful and effective in specific population of patients and reduce the number of treatment sessions needed to obtain an objective response.